2021
DOI: 10.12782/specdiv.26.49
|View full text |Cite
|
Sign up to set email alerts
|

Two New Species of Free-living Marine Nematodes (Nematoda: Axonolaimidae and Tripyloididae) from the Coast of Antarctica

Abstract: Two new species of free-living marine nematodes, Odontophora odontophoroides sp. nov. and Parabathylaimus jare sp. nov., are described from the coastal sand of Langhovde, Lützow-Holm Bay, Dronning Maud Land, Antarctica. Odontophora odontophoroides sp. nov. is the only species in Odontophora Bütschli, 1874 that has bicuspidate odontia. Odontophora odontophoroides sp. nov. is similar to species in Odontophoroides Boucher and Helléouët, 1977 and Synodontium Cobb, 1920 in having bicuspidate odontia, but differs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A biological dredge onboard the research vessel Rinkai-Maru (Misaki Marine Biological Station, the University of Tokyo) was used to collect the specimens during the 12 th JAMBIO Coastal Organism Joint Survey. The methods used for sorting, fixation, and preparation for differential interference contrast microscopy were previously described by Shimada and Kakui (2019), and the methods used for taking photomicrographs and measurements were previously described by Shimada et al (2021). All examined specimens were deposited in the Invertebrate Collection of Hokkaido University Museum (ICHUM), Sapporo, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…A biological dredge onboard the research vessel Rinkai-Maru (Misaki Marine Biological Station, the University of Tokyo) was used to collect the specimens during the 12 th JAMBIO Coastal Organism Joint Survey. The methods used for sorting, fixation, and preparation for differential interference contrast microscopy were previously described by Shimada and Kakui (2019), and the methods used for taking photomicrographs and measurements were previously described by Shimada et al (2021). All examined specimens were deposited in the Invertebrate Collection of Hokkaido University Museum (ICHUM), Sapporo, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…We considered that these individuals belonged to the same species in the family Oncholaimidae. Three males and four females were permanently mounted in anhydrous glycerin (Shimada et al 2021), observed using a BX51 light microscope (Olympus, Japan) with differential interference contrast, and photographed with an PCM500 digital camera (AS ONE, Japan). One male and one female were dried using the hexamethyldisilazane method (Nation 1983), sputter-coated with gold to a thickness of 20 nm, and observed using an S-3000N scanning electron microscope (SEM; Hitachi, Japan).…”
Section: Sampling and Morphological Observationmentioning
confidence: 99%
“…oxyuris Ditlevsen, 1911, Oncholaimus cf. vesicarius (Wieser, 1959, Wiesoncholaimus jambio Shimada & Kakui, 2021, Adoncholaimus daikokuensis Shimada & Kajihara, 2014, and Adoncholaimus pseudofervidus Shimada & Kajihara, 2014, for phylogenetic analysis (Table 1). Total DNA was extracted using an ISOHAIR extraction kit (NIPPON GENE, Japan) following the protocols described by Tanaka et al (2012) and Iwahori (2014) with minor modifications.…”
Section: Molecular Experimentsmentioning
confidence: 99%